# |
ODE |
CAS classification |
Solved? |
time (sec) |
\[
{}y^{\prime } = y^{2} f \left (x \right )-a \tan \left (\lambda x \right )^{2} \left (a f \left (x \right )-\lambda \right )+a \lambda
\] |
[_Riccati] |
✗ |
359.813 |
|
\[
{}y^{\prime } = y^{2} f \left (x \right )-a \cot \left (\lambda x \right )^{2} \left (a f \left (x \right )-\lambda \right )+a \lambda
\] |
[_Riccati] |
✗ |
373.000 |
|
\[
{}y^{\prime } = y^{2}-f \left (x \right )^{2}+f^{\prime }\left (x \right )
\] |
[_Riccati] |
✓ |
1.112 |
|
\[
{}y^{\prime } = y^{2} f \left (x \right )-f \left (x \right ) g \left (x \right ) y+g^{\prime }\left (x \right )
\] |
[_Riccati] |
✓ |
1.586 |
|
\[
{}y^{\prime } = -f^{\prime }\left (x \right ) y^{2}+f \left (x \right ) g \left (x \right ) y-g \left (x \right )
\] |
[_Riccati] |
✓ |
1.684 |
|
\[
{}y^{\prime } = g \left (x \right ) \left (y-f \left (x \right )\right )^{2}+f^{\prime }\left (x \right )
\] |
[[_1st_order, ‘_with_symmetry_[F(x),G(x)]‘], _Riccati] |
✓ |
1.757 |
|
\[
{}y^{\prime } = \frac {f^{\prime }\left (x \right ) y^{2}}{g \left (x \right )}-\frac {g^{\prime }\left (x \right )}{f \left (x \right )}
\] |
[_Riccati] |
✗ |
2.853 |
|
\[
{}f \left (x \right )^{2} y^{\prime }-f^{\prime }\left (x \right ) y^{2}+g \left (x \right ) \left (y-f \left (x \right )\right ) = 0
\] |
[_Riccati] |
✗ |
3.215 |
|
\[
{}y^{\prime } = f^{\prime }\left (x \right ) y^{2}+a \,{\mathrm e}^{\lambda x} f \left (x \right ) y+a \,{\mathrm e}^{\lambda x}
\] |
[_Riccati] |
✓ |
2.245 |
|
\[
{}y^{\prime } = y^{2} f \left (x \right )+g^{\prime }\left (x \right ) y+a f \left (x \right ) {\mathrm e}^{2 g \left (x \right )}
\] |
[_Riccati] |
✓ |
2.101 |
|
\[
{}y^{\prime } = y^{2}-\frac {f^{\prime \prime }\left (x \right )}{f \left (x \right )}
\] |
[_Riccati] |
✓ |
1.154 |
|
\[
{}y^{\prime } = y^{2}+a^{2} f \left (a x +b \right )
\] |
[_Riccati] |
✗ |
1.276 |
|
\[
{}y^{\prime } = y^{2}+\frac {f \left (\frac {1}{x}\right )}{x^{4}}
\] |
[_Riccati] |
✗ |
1.508 |
|
\[
{}y^{\prime } = y^{2}+\frac {f \left (\frac {a x +b}{c x +d}\right )}{\left (c x +d \right )^{4}}
\] |
[_Riccati] |
✗ |
3.763 |
|
\[
{}x^{2} y^{\prime } = x^{4} f \left (x \right ) y^{2}+1
\] |
[_Riccati] |
✗ |
2.529 |
|
\[
{}x^{2} y^{\prime } = y^{2} x^{4}+x^{2 n} f \left (a \,x^{n}+b \right )-\frac {n^{2}}{4}+\frac {1}{4}
\] |
[_Riccati] |
✗ |
5.615 |
|
\[
{}y^{\prime } = y^{2} f \left (x \right )+g \left (x \right ) y+h \left (x \right )
\] |
[_Riccati] |
✗ |
2.373 |
|
\[
{}y^{\prime } = y^{2}+{\mathrm e}^{2 \lambda x} f \left ({\mathrm e}^{\lambda x}\right )-\frac {\lambda ^{2}}{4}
\] |
[_Riccati] |
✗ |
3.007 |
|
\[
{}y^{\prime } = y^{2}-\frac {\lambda ^{2}}{4}+\frac {{\mathrm e}^{2 \lambda x} f \left (\frac {a \,{\mathrm e}^{\lambda x}+b}{c \,{\mathrm e}^{\lambda x}+d}\right )}{\left (c \,{\mathrm e}^{\lambda x}+d \right )^{4}}
\] |
[_Riccati] |
✗ |
45.047 |
|
\[
{}y^{\prime } = y^{2}-\lambda ^{2}+\frac {f \left (\coth \left (\lambda x \right )\right )}{\sinh \left (\lambda x \right )^{4}}
\] |
[_Riccati] |
✗ |
37.645 |
|
\[
{}y^{\prime } = y^{2}-\lambda ^{2}+\frac {f \left (\tanh \left (\lambda x \right )\right )}{\cosh \left (\lambda x \right )^{4}}
\] |
[_Riccati] |
✗ |
19.056 |
|
\[
{}x^{2} y^{\prime } = x^{2} y^{2}+f \left (a \ln \left (x \right )+b \right )+\frac {1}{4}
\] |
[_Riccati] |
✗ |
2.317 |
|
\[
{}y^{\prime } = y^{2}+\lambda ^{2}+\frac {f \left (\cot \left (\lambda x \right )\right )}{\sin \left (\lambda x \right )^{4}}
\] |
[_Riccati] |
✗ |
105.461 |
|
\[
{}y^{\prime } = y^{2}+\lambda ^{2}+\frac {f \left (\tan \left (\lambda x \right )\right )}{\cos \left (\lambda x \right )^{4}}
\] |
[_Riccati] |
✗ |
25.556 |
|
\[
{}y^{\prime } = y^{2}+\lambda ^{2}+\frac {f \left (\frac {\sin \left (\lambda x +a \right )}{\sin \left (\lambda x +b \right )}\right )}{\sin \left (\lambda x +b \right )^{4}}
\] |
[_Riccati] |
✗ |
453.227 |
|
\[
{}y y^{\prime }-y = A
\] |
[_quadrature] |
✓ |
1.140 |
|
\[
{}y y^{\prime }-y = A x +B
\] |
[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]] |
✓ |
8.389 |
|
\[
{}y y^{\prime }-y = -\frac {2 x}{9}+A +\frac {B}{\sqrt {x}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
8.074 |
|
\[
{}y y^{\prime }-y = 2 A \left (\sqrt {x}+4 A +\frac {3 A^{2}}{\sqrt {x}}\right )
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
5.831 |
|
\[
{}y y^{\prime }-y = A x +\frac {B}{x}-\frac {B^{2}}{x^{3}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
1.395 |
|
\[
{}y y^{\prime }-y = A \,x^{k -1}-k B \,x^{k}+k \,B^{2} x^{2 k -1}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
2.321 |
|
\[
{}y y^{\prime }-y = \frac {A}{x}-\frac {A^{2}}{x^{3}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
1.149 |
|
\[
{}y y^{\prime }-y = A +B \,{\mathrm e}^{-\frac {2 x}{A}}
\] |
[[_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
1.374 |
|
\[
{}y y^{\prime }-y = A \left ({\mathrm e}^{\frac {2 x}{A}}-1\right )
\] |
[[_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
1.309 |
|
\[
{}y y^{\prime }-y = -\frac {2 \left (m +1\right )}{\left (m +3\right )^{2}}+A \,x^{m}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
1.960 |
|
\[
{}y y^{\prime }-y = -\frac {2 x}{9}+6 A^{2} \left (1+\frac {2 A}{\sqrt {x}}\right )
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
6.420 |
|
\[
{}y y^{\prime }-y = \frac {2 m -2}{\left (m -3\right )^{2}}+\frac {2 A \left (m \left (m +3\right ) \sqrt {x}+\left (4 m^{2}+3 m +9\right ) A +\frac {3 m \left (m +3\right ) A^{2}}{\sqrt {x}}\right )}{\left (m -3\right )^{2}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
39.916 |
|
\[
{}y y^{\prime }-y = \frac {\left (2 m +1\right ) x}{4 m^{2}}+\frac {A}{x}-\frac {A^{2}}{x^{3}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
1.874 |
|
\[
{}y y^{\prime }-y = \frac {4}{9} x +2 A \,x^{2}+2 A^{2} x^{3}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
1.354 |
|
\[
{}y y^{\prime }-y = -\frac {3 x}{16}+\frac {5 A}{x^{{1}/{3}}}-\frac {12 A^{2}}{x^{{5}/{3}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
4.155 |
|
\[
{}y y^{\prime }-y = \frac {A}{x}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
0.651 |
|
\[
{}y y^{\prime }-y = -\frac {x}{4}+\frac {A \left (\sqrt {x}+5 A +\frac {3 A^{2}}{\sqrt {x}}\right )}{4}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
7.792 |
|
\[
{}y y^{\prime }-y = \frac {2 a^{2}}{\sqrt {8 a^{2}+x^{2}}}
\] |
[[_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
2.319 |
|
\[
{}y y^{\prime }-y = 2 x +\frac {A}{x^{2}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
0.972 |
|
\[
{}y y^{\prime }-y = -\frac {6 X}{25}+\frac {2 A \left (2 \sqrt {x}+19 A +\frac {6 A^{2}}{\sqrt {x}}\right )}{25}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
27.727 |
|
\[
{}y y^{\prime }-y = \frac {3 x}{8}+\frac {3 \sqrt {a^{2}+x^{2}}}{8}-\frac {a^{2}}{16 \sqrt {a^{2}+x^{2}}}
\] |
[[_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
5.269 |
|
\[
{}y y^{\prime }-y = -\frac {4 x}{25}+\frac {A}{\sqrt {x}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
4.934 |
|
\[
{}y y^{\prime }-y = -\frac {9 x}{100}+\frac {A}{x^{{5}/{3}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
40.636 |
|
\[
{}y y^{\prime }-y = -\frac {12 x}{49}+\frac {2 A \left (5 \sqrt {x}+34 A +\frac {15 A^{2}}{\sqrt {x}}\right )}{49}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
7.279 |
|
\[
{}y y^{\prime }-y = -\frac {12 x}{49}+\frac {A \left (25 \sqrt {x}+41 A +\frac {10 A^{2}}{\sqrt {x}}\right )}{98}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
7.194 |
|
\[
{}y y^{\prime }-y = -\frac {2 x}{9}+\frac {A}{\sqrt {x}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
4.704 |
|
\[
{}y y^{\prime }-y = -\frac {5 x}{36}+\frac {A}{x^{{7}/{5}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
47.919 |
|
\[
{}y y^{\prime }-y = -\frac {12 x}{49}+\frac {6 A \left (-3 \sqrt {x}+23 A +\frac {12 A^{2}}{\sqrt {x}}\right )}{49}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
7.126 |
|
\[
{}y y^{\prime }-y = -\frac {30 x}{121}+\frac {3 A \left (21 \sqrt {x}+35 A +\frac {6 A^{2}}{\sqrt {x}}\right )}{242}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
7.221 |
|
\[
{}y y^{\prime }-y = -\frac {3 x}{16}+\frac {A}{x^{{5}/{3}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
39.997 |
|
\[
{}y y^{\prime }-y = -\frac {12 x}{49}+\frac {4 A \left (-10 \sqrt {x}+27 A +\frac {10 A^{2}}{\sqrt {x}}\right )}{49}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
6.500 |
|
\[
{}y y^{\prime }-y = \frac {A}{\sqrt {x}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
1.724 |
|
\[
{}y y^{\prime }-y = \frac {A}{x^{2}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
0.732 |
|
\[
{}y y^{\prime }-y = A \left (n +2\right ) \left (\sqrt {x}+2 \left (n +2\right ) A +\frac {\left (n +1\right ) \left (n +3\right ) A^{2}}{\sqrt {x}}\right )
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
17.169 |
|
\[
{}y y^{\prime }-y = A \left (n +2\right ) \left (\sqrt {x}+2 \left (n +2\right ) A +\frac {\left (2 n +3\right ) A^{2}}{\sqrt {x}}\right )
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
19.791 |
|
\[
{}y y^{\prime }-y = A \sqrt {x}+2 A^{2}+\frac {B}{\sqrt {x}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
11.220 |
|
\[
{}y y^{\prime }-y = 2 A^{2}-A \sqrt {x}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
2.016 |
|
\[
{}y y^{\prime }-y = -\frac {x}{4}+\frac {6 A \left (\sqrt {x}+8 A +\frac {5 A^{2}}{\sqrt {x}}\right )}{49}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
7.161 |
|
\[
{}y y^{\prime }-y = -\frac {6 x}{25}+\frac {6 A \left (2 \sqrt {x}+7 A +\frac {4 A^{2}}{\sqrt {x}}\right )}{25}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
6.636 |
|
\[
{}y y^{\prime }-y = -\frac {3 x}{16}+\frac {3 A}{x^{{1}/{3}}}-\frac {12 A^{2}}{x^{{5}/{3}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
4.965 |
|
\[
{}y y^{\prime }-y = \frac {3 x}{8}+\frac {3 \sqrt {b^{2}+x^{2}}}{8}+\frac {3 b^{2}}{16 \sqrt {b^{2}+x^{2}}}
\] |
[[_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
5.057 |
|
\[
{}y y^{\prime }-y = \frac {9 x}{32}+\frac {15 \sqrt {b^{2}+x^{2}}}{32}+\frac {3 b^{2}}{64 \sqrt {b^{2}+x^{2}}}
\] |
[[_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
6.453 |
|
\[
{}y y^{\prime }-y = -\frac {3 x}{32}-\frac {3 \sqrt {a^{2}+x^{2}}}{32}+\frac {15 a^{2}}{64 \sqrt {a^{2}+x^{2}}}
\] |
[[_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
5.589 |
|
\[
{}y y^{\prime }-y = A \,x^{2}-\frac {9}{625 A}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
0.931 |
|
\[
{}y y^{\prime }-y = -\frac {6}{25} x -A \,x^{2}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
0.901 |
|
\[
{}y y^{\prime }-y = \frac {6}{25} x -A \,x^{2}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
0.905 |
|
\[
{}y y^{\prime }-y = 12 x +\frac {A}{x^{{5}/{2}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
5.219 |
|
\[
{}y y^{\prime }-y = \frac {63 x}{4}+\frac {A}{x^{{5}/{3}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
45.341 |
|
\[
{}y y^{\prime }-y = 2 x +2 A \left (10 \sqrt {x}+31 A +\frac {30 A^{2}}{\sqrt {x}}\right )
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
7.043 |
|
\[
{}y y^{\prime }-y = 2 x +2 A \left (-10 \sqrt {x}+19 A +\frac {30 A^{2}}{\sqrt {x}}\right )
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
6.215 |
|
\[
{}y y^{\prime }-y = -\frac {28 x}{121}+\frac {2 A \left (5 \sqrt {x}+106 A +\frac {65 A^{2}}{\sqrt {x}}\right )}{121}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
7.110 |
|
\[
{}y y^{\prime }-y = -\frac {12 x}{49}+\frac {A \left (5 \sqrt {x}+262 A +\frac {65 A^{2}}{\sqrt {x}}\right )}{49}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
7.160 |
|
\[
{}y y^{\prime }-y = -\frac {12 x}{49}+A \sqrt {x}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
3.964 |
|
\[
{}y y^{\prime }-y = 6 x +\frac {A}{x^{4}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
0.898 |
|
\[
{}y y^{\prime }-y = 20 x +\frac {A}{\sqrt {x}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
4.696 |
|
\[
{}y y^{\prime }-y = \frac {15 x}{4}+\frac {A}{x^{7}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
0.957 |
|
\[
{}y y^{\prime }-y = -\frac {10 x}{49}+\frac {2 A \left (4 \sqrt {x}+61 A +\frac {12 A^{2}}{\sqrt {x}}\right )}{49}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
6.430 |
|
\[
{}y y^{\prime }-y = -\frac {12 x}{49}+\frac {2 A \left (\sqrt {x}+166 A +\frac {55 A^{2}}{\sqrt {x}}\right )}{49}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
7.105 |
|
\[
{}y y^{\prime }-y = -\frac {4 x}{25}+\frac {A \left (7 \sqrt {x}+49 A +\frac {6 A^{2}}{\sqrt {x}}\right )}{50}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
6.914 |
|
\[
{}y y^{\prime }-y = \frac {15 x}{4}+\frac {6 A}{x^{{1}/{3}}}-\frac {3 A^{2}}{x^{{5}/{3}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
4.131 |
|
\[
{}y y^{\prime }-y = -\frac {3 x}{16}+\frac {A}{x^{{1}/{3}}}+\frac {B}{x^{{5}/{3}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
15.298 |
|
\[
{}y y^{\prime }-y = -\frac {5 x}{36}+\frac {A}{x^{{3}/{5}}}-\frac {B}{x^{{7}/{5}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
9.079 |
|
\[
{}y y^{\prime }-y = \frac {k}{\sqrt {A \,x^{2}+B x +c}}
\] |
[[_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
3.876 |
|
\[
{}y y^{\prime }-y = -\frac {12 x}{49}+3 A \left (\frac {1}{49}+B \right ) \sqrt {x}+3 A^{2} \left (\frac {4}{49}-\frac {5 B}{2}\right )+\frac {15 A^{3} \left (\frac {1}{49}-\frac {5 B}{4}\right )}{4 \sqrt {x}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
5.106 |
|
\[
{}y y^{\prime }-y = -\frac {6 x}{25}+\frac {4 B^{2} \left (\left (2-A \right ) x^{{1}/{3}}-\frac {3 B \left (2 A +1\right )}{2}+\frac {B^{2} \left (1-3 A \right )}{x^{{1}/{3}}}-\frac {A \,B^{3}}{x^{{2}/{3}}}\right )}{75}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
6.966 |
|
\[
{}y y^{\prime }-y = \frac {3 x}{4}-\frac {3 A \,x^{{1}/{3}}}{2}+\frac {3 A^{2}}{4 x^{{1}/{3}}}-\frac {27 A^{4}}{625 x^{{5}/{3}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
8.249 |
|
\[
{}y y^{\prime }-y = -\frac {6 x}{25}+\frac {7 A \,x^{{1}/{3}}}{5}+\frac {31 A^{2}}{3 x^{{1}/{3}}}-\frac {100 A^{4}}{3 x^{{5}/{3}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
8.040 |
|
\[
{}y y^{\prime }-y = -\frac {10 x}{49}+\frac {13 A^{2}}{5 x^{{1}/{5}}}-\frac {7 A^{3}}{20 x^{{4}/{5}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
14.849 |
|
\[
{}y y^{\prime }-y = -\frac {33 x}{169}+\frac {286 A^{2}}{3 x^{{5}/{11}}}-\frac {770 A^{3}}{9 x^{{13}/{11}}}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
37.519 |
|
\[
{}y y^{\prime }-y = -\frac {21 x}{100}+\frac {7 A^{2} \left (\frac {123}{x^{{1}/{7}}}+\frac {280 A}{x^{{5}/{7}}}-\frac {400 A^{2}}{x^{{9}/{7}}}\right )}{9}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class B‘]] |
✗ |
32.616 |
|
\[
{}y y^{\prime }-y = a x +b \,x^{m}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
1.605 |
|
\[
{}y y^{\prime }-y = -\frac {\left (m +1\right ) x}{\left (m +2\right )^{2}}+A \,x^{2 m +1}+B \,x^{3 m +1}
\] |
[_rational, [_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
12.206 |
|
\[
{}y y^{\prime }-y = a^{2} \lambda \,{\mathrm e}^{2 \lambda x}-a \left (b \lambda +1\right ) {\mathrm e}^{\lambda x}+b
\] |
[[_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
2.701 |
|
\[
{}y y^{\prime }-y = a^{2} \lambda \,{\mathrm e}^{2 \lambda x}+a \lambda x \,{\mathrm e}^{\lambda x}+b \,{\mathrm e}^{\lambda x}
\] |
[[_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
2.227 |
|
\[
{}y y^{\prime }-y = 2 a^{2} \lambda \sin \left (2 \lambda x \right )+2 a \sin \left (\lambda x \right )
\] |
[[_Abel, ‘2nd type‘, ‘class A‘]] |
✗ |
7.118 |
|